Socjologia wychowania w systemie nauki o społeczeństwie - Włodarek, Jan (Wydział Prawa i Administracji UAM, 1987)
The article deals with the issue of the place of sociology of education in the structure of sociology. The analysis is centered first of all on the relations between the sociology of education and general sociology and between the sociology of education and the branches of so-called particular sociology. Basing on the analysis of origin and history of development of the sociology of education and on the analysis of views and standpoints of the founders of that branch (F. Znaniecki, T. Geiger and others) as well as on the basis of the research practice, the author reveals a close relationship between the sociology of education as a sociological theory of education and general sociology, or better: general sociologies corresponding to great theoretical systems of modern socjology: Marxist, structural-functional, so-called humanistic sociology, etc. On the other hand, the author distinguishes between the sociology of education and so-called educational sociology as well as various types of social pedagogics, considering them to be normatively and practically oriented sociological or pedagogical studies. The sociology of education develops the empirical studies of education on the basis of sociological theory, especially the sociological theory of education. Besides, the development of these studies is the condition of the development of the theory of education. In the studies of education the sociology of education uses the results of all other branches of sociology as well as of other educational sciences.
Sociology of Education in the Structure of Sociology